2022
DOI: 10.3389/fnagi.2022.1052765
|View full text |Cite
|
Sign up to set email alerts
|

Potential blood biomarkers for chronic traumatic encephalopathy: The multi-omics landscape of an observational cohort

Abstract: Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease associated with exposure to repetitive head impacts, which is susceptible in elderly people with declined mobility, athletes of full contact sports, military personnel and victims of domestic violence. It has been pathologically diagnosed in brain donors with a history of repetitive mild traumatic brain injury (rmTBI), but cannot be clinically diagnosed for a long time. By the continuous efforts by neuropathologists, neurologists and neurosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…For example, In a single‐center observational cohort study (NCT04928534), serum exosomes CHL1, KIF2A, miR‐1183, and miR‐297 were found to be potential biomarkers of CTE in patients with repetitive mild traumatic brain injury. 370 A previous prospective, multicenter clinical utility study of the ExoDx Prostate test as a predictor of prognosis in high‐grade prostate cancer (NCT03235687) showed that the ExoDx Prostate (EPI) test had a significant impact on prostate biopsy decisions. 371 The team recently reported interim results with 2.5 years of follow‐up, suggesting that prebiopsy EPI testing also leads to better outcomes when followed for 2.5 years after the initial biopsy decision‐making process.…”
Section: Clinical Applications and Challengesmentioning
confidence: 99%
“…For example, In a single‐center observational cohort study (NCT04928534), serum exosomes CHL1, KIF2A, miR‐1183, and miR‐297 were found to be potential biomarkers of CTE in patients with repetitive mild traumatic brain injury. 370 A previous prospective, multicenter clinical utility study of the ExoDx Prostate test as a predictor of prognosis in high‐grade prostate cancer (NCT03235687) showed that the ExoDx Prostate (EPI) test had a significant impact on prostate biopsy decisions. 371 The team recently reported interim results with 2.5 years of follow‐up, suggesting that prebiopsy EPI testing also leads to better outcomes when followed for 2.5 years after the initial biopsy decision‐making process.…”
Section: Clinical Applications and Challengesmentioning
confidence: 99%
“…They also observed that most miRNAs were circulating freely in plasma, which supports the use of plasma without the need for EVs isolation. Ge et al [ 120 ] compared serum and exosome biomarkers between 12 patients with a history of rTBIs and, thus, a different likelihood of CTE and respective controls, distinguishing serum and exosomal miR-1183 and exosomal miR-297 as potential diagnostic miRNA biomarkers of CTE. Neither of these studies related miRNA expression to neurobehavioral or imaging evidence.…”
Section: Micro Rna Biomarkers In Ctementioning
confidence: 99%